PENERAPAN PRA LITERASI MENGGUNAKAN METODE BERMAIN PADA ANK USIA DINI - Sahrul Salingkat (Damhil Education Journal, 2023)
The play method is an approach to always create an enjoyable atmosphere for students in the pre-literacy process. Pre-literacy is an important first step in developing literacy skills in children before they actually learn to read and write. This study aims to apply the play method in pre-literacy learning for students at TK Negeri I Banggai Utara. In this study using qualitative research involved in the research consisted of teachers at TK Negeri I Banggai Utara and early childhood in the class and also parents. In collecting data using observation, interviews, and also documentation. The results of the study provide an indication that early literacy learning has a positive impact on early childhood at TK Negeri I Banggai Utara. Children show greater interest in learning activities and are more active in participating in the pre-literacy process. The play method also helps improve children's creativity, imagination and social interaction.